Calculation of Radon Gas Concentrations and Effective Dose of Al-Hindia, Euphrates River in Karbala Governorate Using RAD7 - Obied, Tagreed A.; Oleiwi, Mohanad H. (Iraqi Journal of Science, 2024)
In this research, the radon gas concentration was measured for samples from the water of the Euphrates River in the Hindia district of Karbala governorate. The selected collection locations were 30 different local ones on the river between the ancient and modern bridges, heading north and south, respectively; the distance between locations was 100 meters. The concentrations and effective dose of radon were measured using the RAD7 device technology. The highest value was for sample 21, where the effective dose was (0.00001752 Bq/m3). The same value for the effective dose was of sample 7. The lowest value was in sample 27, where the effective dose was (0 Bq/m3), the same value of sample 3. It was observed from the study that the remaining values of the samples ranged from sample 1 as the lowest value of the effective dose (0.0799 Bq/m3) and also for sample 2 and sample 15. The highest value was for samples 29 and 23, where the value of the effective dose was (0.00001314 Bq/m3). However, from observing the results, these values are within the internationally permissible limits according to the recommendations of   US Environmental Protection Agency, which is 11 Bq/ L.